Teenagers and young adults with cancer in Europe: from national programmes to a European integrated coordinated project - Stark, D; Bielack, S; Brugieres, L; Dirksen, U; Duarte, X; Dunn, S; Erdelyi, D J; Grew, T; Hjorth, L; Jazbec, J; Kabickova, E; Konsoulova, A; et al. (European journal of cancer care, 2016)
Over 14 000 patients aged 15-24 are estimated to be diagnosed with cancer in the European Union (EU) each year. Teenagers and young adults (TYA) often fall down gaps between children's and adults cancer services. The specific challenges of providing optimal care to them are described, but we present a summary of recent progress. Progress to overcome these challenges is happening at different rates across Europe. We summarise the European national projects in this field but more recently we have seen the beginnings of European coordination. Within the EU 7th Funding Programme (FP7) European Network for Cancer Research in Children and Adolescents programme (ENCCA), a specific European Network for Teenagers and Young Adults with Cancer has held a series of scientific meetings, including professionals, patients and caregivers. This group has proposed unanswered research questions and agreed key features of a high-quality service that can improve outcomes for TYA with cancer, including the primacy of collaboration between adult and paediatric services to eliminate the gap in the management of TYA with cancer.
Keywords: Humans; mladý dospělý; lidé; Europe; mezinárodní spolupráce; International Cooperation; Evropská unie; Delivery of Health Care; Adolescent; biomedicínský výzkum; lékařská onkologie; Neoplasms; poskytování zdravotní péče; nádory; Young Adult; Biomedical Research; Evropa; mladiství; European Union; Medical Oncology